Development and validation of the chromatography-mass spectrometry technique for polyprenols quantitative assessment - N. S. Popov; A. A. Antipina; S. V. Savintsev; V. Y. Balabanyan (Разработка и регистрация лекарственных средств)
Introduction. Polyprenols are known as a class of natural long-chain isoprenoid alcohols, which are natural bioregulators that directly participate in the synthesis of cell membrane glycoproteins. Their hepatoprotective activity is proven, as well other types of their pharmacological effects are known, which is the reason of significant interest in these substances as a promising medicinal product. It is non-trivial task to determine the sum of polyprenols in extracts as include design and implementation of accurate reproducible analytical methods, which will subsequently be used in standardization.Aim. Development and validation of the chromatographic-mass spectrometric technique for polyprenols identification and their quantitative assessment.Materials and methods. Chromatographic separation of polyprenols was performed by using an HPLC Agilent 1260 Infinity II (Agilent Technologies, США); with the mixture of methanol, n-hexane, propanol-2, and aqueous ammonium acetate solution as eluent in gradient mode. An AB Sciex QTrap® 3200MD (AB Sciex Pte. Ltd., Singapore) triple quadrupole mass spectrometer was used as a detector, with the registration of polyprenols adducts.Results and discussion. The conditions for chromatographic separation and detection of polyprenols were identified. The developed technique was validated for the following characteristics: specificity, limit of detection, limit of quantification, linearity, accuracy, precision, range of application, and stability.Conclusion. It was determined the content of polyprenols in the substance recieved from Ginkgo biloba L. and Picea abies L. The developed technique can be used in the future to assess the content of polyprenols in drug products or pharmaceutical substances.